The investment decision on Unggul Day Care (child care centers) at Indonesian Finance Business Plan - Candra Saputra; Tantri Yanuar Rahmat Syah; Samerdanta Pusaka; Rokiah Kusumapradja (Journal of Multidisciplinary Academic, 2021)
The decision to invest on day care is seen by amount levels of childcare demand at office area. In this case, a parent is busy to working at office with earning enough salary also they can monitor child development directly. Thus, in this study, working parents can entrust and get education for their children. Here, we achieve the greatest investment with services based on renting or using a private home as a day care centre business ground, and make sure using comply with local laws.